Muscle cross-sectional areas and performance power of limbs and trunk in the rowing motion - Tachibana, K.; Yashiro, K.; Miyazaki, J.; Ikegami, Y.; Higuchi, M. (Sports Biomechanics, 2007)
Although it is clear that rowers have a large muscle mass, their distribution of muscle mass and which of the main motions in rowing mediates muscle hypertrophy in each body part are unclear. We examine the relationships between partial motion power in rowing and muscle cross-sectional area of the thigh, lower back, and upper arms. Sixty young rowers (39 males and 21 females) participated in the study. Joint positions and forces were measured by video cameras and rowing ergometer software, respectively. One-dimensional motion analysis was performed to calculate the power of leg drive, trunk swing, and arm pull motions. Muscle cross-sectional areas were measured using magnetic resonance imaging. Multiple regression analyses were carried out to determine the association of different muscle cross-sectional areas with partial motion power. The anterior thigh best explained the power demonstrated by leg drive (r2 = 0.508), the posterior thigh and lower back combined best explained the power demonstrated by the trunk swing (r2 = 0.493), and the elbow extensors best explained the power demonstrated by the arm pull (r2 = 0.195). Other correlations, such as arm muscles with leg drive power (r2 = 0.424) and anterior thigh with trunk swing power (r2 = 0.335), were also significant. All muscle cross-sectional areas were associated with rowing performance either through the production of power or by transmitting work. The results imply that rowing motion requires a well-balanced distribution of muscle mass throughout the body.